Transformation Of Law And Legal Consciousness In Transitive Societies In Globalized World - Орденов, С. С. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2019)
Introduction. The legal systems of different countries in a globalized world are unified by norms of international law. In this context the question arises: are countries integrating into the globalized community capable of ensuring the practical implementation of international legal obligations into their legal systems? It determines the aim and the tasks which are to define the key structural components causing the transformation of law and legal consciousness in transitive societies in a globalized world. Research methods are structural-functional, socio-cultural and comparative approaches in their dialectical unity. Research results: in our study we assume that the functions of law determine the existing type of society, which in turn influences the whole set of legal relations and is reflected in the manifestations of law and legal consciousness. Taken into account that in transitive societies, the transition to a liberal system of relations has not occurred, the functions of the legal mechanism become dysfunctional in nature, and the laws do not meet the criteria of justice. In such circumstances, dissimulation of law is rooting in the social space while support and production of fiction becomes the only one single possible sociality. Discussion. In transitive societies, a paternalistic mechanism of "securing" rights as privileges (Berman) is dominant. As a result, the rights are nullified, not reproduced at the level of being and, ultimately, do not reach the average citizen. On the grounds of impossibility of securing the law in the real life, the political and legal discourse of transitive societies affirms a manipulative component aimed at implanting the simulacra of the legal space. The very manipulation is used by the authorities as a mechanism for asserting non-law in the society. Conclusion. Despite the unification of the legal systems of different countries in accordance with the requirements of international law, people in most transitive societies of the traditionalist type continue to be trapped in the tribalism of interpersonal relationships. In such circumstances, the implementation of any legal ideas in the legislative system of the transitive countries becomes in practice prohibitive and repressive.